Designing Interactive Systems Conference 2022
DOI: 10.1145/3532106.3533480
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Gestures for Novel Note-taking Interactions

Abstract: Handwriting recognition is improving in leaps and bounds, and this opens up new opportunities for stylus-based interactions. In particular, note-taking applications can become a more intelligent user interface, incorporating new features like autocomplete and integrated search. In this work we ran a gesture elicitation study, asking 21 participants to imagine how they would interact with an imaginary, intelligent note-taking application. Participants were prompted to produce gestures for common actions such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Integrating note-taking features into VR applications enables students to engage in deep information processing and achieve their full potential. In addition to facilitating memory recall, recent research has also shown the positive impacts of note-taking applications on academic success, in encouraging individual learning responsibility [114], increasing participants' social interaction quality [22,30], and assimilating large information [79,92].…”
Section: Integrating Note-taking Feature Into Vr Lectures Can Strengthenmentioning
confidence: 99%
“…Integrating note-taking features into VR applications enables students to engage in deep information processing and achieve their full potential. In addition to facilitating memory recall, recent research has also shown the positive impacts of note-taking applications on academic success, in encouraging individual learning responsibility [114], increasing participants' social interaction quality [22,30], and assimilating large information [79,92].…”
Section: Integrating Note-taking Feature Into Vr Lectures Can Strengthenmentioning
confidence: 99%